Pavlenko N. Gender component in the meaning of English phraseological units - Pavlenko N. (Philological Treatises, 2020)
Gender, which represents a product of social and cultural production, is present in all structures and levels of language. But representation of gender in idioms gives wider and clearer understanding of the roles performed by women and men in a particular society. This article focuses on studying the gender component in the meaning of English phraseological units. А brief overview of the theory concerning phraseological units with gender component is given. The attention is focused on the origin of the term ‘gender’. Phraseological units with gender component are a very important source of information and reveal the most relevant problems of the present time.